PENGARUH PEMBELAJARAN MODEL BERMAIN TERHADAP KETERAMPILAN PASSING BAWAH BOLA VOLI MINI - Mita Erliana (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2014)
The Influence Of Learning Model Under The Passing Skills Of Playing Volleyball Miniature. the purpose of this research is to know the influence of learning model under the passing skills of playing volleyball mini on participant sample class IV Stage of elementary school Sungai Besar 2 Banjarbaru.The research method is experimentation. The population in the study are learners learner class IV Stage of elementary school Sungai Besar 2 Banjarbaru that add up to 20 people. Sampling techniques using the technique of total sampling. Then do a test early (pre-test), were given treatment (treatment) and the ultimate test (post-test).The researchresults of t count (11, 68) > t table (2,093) and average value of pre - test passing down 4.99 average rating, post-test 7.55 to the percentage increase of 52%. Conclusions in this study that there is influence the learning model under the passing skills of playing volleyball mini learners class IV Stage of elementary school   Sungai Besar 2Banjarbaru. Keywords: Model play, passing under the mini volleyball